Modal Sosial Pedagang Buah di Pasar Pagi Cik Puan Kota Pekanbaru - Ermayanti Ermayanti; Achmad Hidir (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research was conducted on fruit traders at Ms. Puan’s Morning Market, Pekanbaru citywith the aim of knowing how the social capital of fruit traders at Ms. Puan’s Morning Market, Pekanbaru city.This research was conducted on fruit traders at the Ms. Puan morning market in Pekanbaru City with the aim of knowing how the social capital of fruit traders is.this study uses a descriptive qualitative research method. Research subjects in this study amounted to 5 (five) informants. The technique of determining informants, namely by using purposive sampling technique is to take subjects by specifying special characteristics with the aim of research that is expected to be able to answer research problems. In collecting data researchers used observation techniques, interviews, and documentation. The theory is the theory of social capital put forward by Jhon Field which consists of social networks, beliefs, and norms. The results of this study are that social capital is very important in running a business and the smooth running of fruit business at Ms. Puan morning market pekanbaru city, such as a network that can help or facilitate the smooth running of their business. Trust that makkes it easier for them to sell fruit, with social capital such as a network of trust and norms, fruit sellers can maintain fruit and make their business easier because managing a business is carried out jointly and sense of trust is established. Social norms that are intertwined becomen a benchmark and make them more focused